2021
DOI: 10.5194/egusphere-egu21-2239
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Digital soil mapping of soil fertility index for agricultural lands in tropical environment

Abstract: <p>Indicators of soil production function such as soil fertility index can potentially be a key decision tool in spatial planning for sustainable land management. The establishment of such soil fertility index requires basic soil properties which can be modelled for spatial mapping. The objective of this study was to take advantage of the soil legacy data of Benin to produce a digital soil map of soil fertility index at a national scale based on 8 soil properties (soil organic carbon matter, nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…PTFs based on random forest showed that clay and sand were the predictor variable most important in the prediction, and higher value of R 2 associated with w 330 prediction, medium value with w 15000 prediction, and lower value with w 0 prediction. The use of PTFs represents a useful tool, a low-cost method, and an easy technique to estimate soil hydraulic properties, to evaluate soil water retention capacity, and to optimize water management for farmers Hounkpatin et al, 2022.…”
Section: Discussionmentioning
confidence: 99%
“…PTFs based on random forest showed that clay and sand were the predictor variable most important in the prediction, and higher value of R 2 associated with w 330 prediction, medium value with w 15000 prediction, and lower value with w 0 prediction. The use of PTFs represents a useful tool, a low-cost method, and an easy technique to estimate soil hydraulic properties, to evaluate soil water retention capacity, and to optimize water management for farmers Hounkpatin et al, 2022.…”
Section: Discussionmentioning
confidence: 99%